2011
DOI: 10.1021/jp111852s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Structural Parameters of Protein-Containing Reverse Micellar Solution by Near-Infrared Absorption Spectroscopy

Abstract: We present a method based on near-infrared absorption spectroscopy of the OH stretching vibration band of water around 3400 cm(-1) to examine whether the aqueous cavity size of a protein-unfilled reverse micelle is affected by solubilization of protein, and it has been found for AOT [= bis(2-ethylhexyl)sulfosuccinate] reverse micellar solution with myoglobin that the cavity size does not change before and after solubilization of the protein at water-to-surfactant molar ratios (w(0)) from 2 to ∼18; that is, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
5
24
0
Order By: Relevance
“…A reverse micellar solution was prepared using the injection method [23]. AOT (Sigma-Aldrich), isooctane (Wako), and sterile Milliporefiltered water (Yamato) were used as the surfactant, oil, and water, respectively.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…A reverse micellar solution was prepared using the injection method [23]. AOT (Sigma-Aldrich), isooctane (Wako), and sterile Milliporefiltered water (Yamato) were used as the surfactant, oil, and water, respectively.…”
Section: Samplementioning
confidence: 99%
“…Accordingly, the structure and dynamics of water in reverse micelles have been extensively studied through various experimental methods, and these studies have revealed that the water's features are quite different from those of liquid water and depend on the size of the reverse micelles [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. On the other hand, reverse micelles are considered good models of cells, because biomolecules, such as proteins and DNA, can be dissolved in them [2,[20][21][22][23]. Water plays an important role in the function of biomolecules, and the condition of water in cells is different from that in a dilute aqueous solution of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…A concern at the outset might be that enzymes tend to be much larger than reverse micelles. However, reverse micelles readily fuse as necessary to encapsulate enzymes, and they retain their w 0 in so doing [36]. …”
Section: Applicationsmentioning
confidence: 99%
“…A reverse micelle is a nanometer-scale cage filled with water [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The aqueous cavity radius of the reverse micelle is proportional to the water-surfactant molar ratio w 0 (=[water]/[surfactant]), and can be controlled experimentally [11,12].…”
Section: Introductionmentioning
confidence: 99%